A compreensão da metáfora por aprendizes de português como língua adicional em contexto acadêmico - Presotto, Leticia (2020)
The study of metaphor from a teaching perspective has been developed for a long time, but it remains a relatively new topic in the area of additional language teaching (LOW, 2008; FERREIRA, 2007; LITTLEMORE; LOW, 2006; BOERS, 2000). According to Low (2008), the use of cognitive theories about metaphors should not be indiscriminate, but related to research on alternative methods of teaching metaphor and on metaphorical skills that should be acquired by students, especially at the discourse level. An intervention based on metaphor awareness is one of the ways to encourage thinking about the existence of this phenomenon in our daily lives (SAATY, 2016; WAN, 2014; LITTLEMORE, 2004). Concerning academic discourse, metaphor today is understood as a phenomenon that plays a crucial role in this specific context, which has fueled discussions and reflections on its use (HERRMANN, 2013; GIANONNI, 2009; GIBBS, 2008; LITTLEMORE; LOW, 2006). In this sense, this research seeks to verify whether, based on cognitive linguistics, metaphor awareness facilitates the understanding of this phenomenon. In addition, this research aims at investigating specific aspects of metaphor, such as a possible difference in the understanding of primary and complex metaphors, as well as more conventional and less conventional metaphorical mappings. It also seeks to analyze the influence of familiarity of metaphorical linguistic expressions and vocabulary to understand this phenomenon. In order to do so, an experimental study was carried out with Portuguese as additional language (PAL) learners in the context of immersion at a university in the south of Brazil. Participants responded to tasks of understanding metaphor in the academic context, which were applied before and after a metaphor awareness session. The responses of the control and experimental groups (pre and post-intervention) were compared after data collection. Contrary to the hypothesis, awareness of the metaphor did not have the expected effect. It is possible that the time dedicated to the session and the type of task contributed to this result. On the other hand, the characteristics of the metaphors investigated and pointed out by the theory were confirmed by the data analysis. It is believed that this study may contribute to the teaching and learning area of PAL regarding differentiated strategies for working with figurative language, a field still not thoroughly explored in Brazilian Portuguese.